M-KID(MASTITIS KID DETECTION): INOVASI PEMBUATAN DETEKSI MASTITIS YANG DIAPLIKASIKAN PADA PETERNAKAN SAPI PERAH DI KOTA MALANG - Erste Putra, Dimas Rizky (Program Kreativitas Mahasiswa - Karsa Cipta, 2014)
Mastitis is an inflammation internal tissues of the mammary gland and marked by physical and chemical changes in milk quality with or without pathological changes of mammary gland. In subclinical mastitis there are visible sign detected except with a Mastitis detector or mastitis detection methods. Mastitis detection is very expensive for farmers and the reagents are harmful for cows, farmers and the environment. Therefore, it is necessary to develop mastitis detection tool that is easy to use and applicable. This mastitis detection tool using reagents biosurfactant from Pseudomonas sp. which grown in minimum media containing vegetable oil in concentration of 25% and incubation period of 24 hours. M-KID prototype tool made from glass and it is proven that the tool could be use as diagnostic test for subclinical mastitis in dairy cows, it has high level of accuracy and accountable compared to mastitis reagan and mastits tools that have been sold in the market.Key words: Mastitis, Milk, Mastitis detection Equipment, Pseudomonas sp., Biosurfactants